Nilai-Nilai komunikasi dalam Al-Qur’an guna Menjaga Ketahanan Keluarga - Rudhi (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2026)
Family resilience is the primary foundation for building a harmonious and sustainable society. From an Islamic perspective, family resilience is determined not only by economic and social aspects, but also by the quality of communication based on spiritual values. This article aims to analyze the concept of family resilience in Islam and examine the communication values ​​in the Qur'an that play a role in maintaining family resilience. This study uses a library research method by examining verses of the Qur'an, commentaries, and scientific literature relevant to Islamic communication and family resilience. The results show that the concept of family resilience in Islam is built on the principles of sakinah (tranquility), mawaddah (love), and rahmah (compassion), which are realized through effective and ethical communication. Communication values ​​in the Qur'an that support family resilience include qaulan sadidan (truthful words), qaulan ma'rufan (good words), qaulan layyinan (gentle words), qaulan kariman (noble words), and qaulan balighan (imprinting words). These values ​​serve to create harmonious relationships, minimize conflict, and strengthen emotional bonds between family members. Thus, the implementation of Qur'anic communication values ​​is an important key in maintaining and strengthening family resilience in modern life.